Effect of Rhizobium japonicum and phosphorus on nutrient uptake and yield of soybean (Glycine max) in an Ultisol of Manipur hills - RAYCHAUDHURI, MAUSUMI; KUMAR, KAILASH; RAYCHAUDHURI, S (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1994 and 1995 to study the effect of Rhizobium inoculation and phosphorus fertilization on soybean [Glycine max (L.) Merr.] production in an acid hill Ultisol of manipur. Rhizobium inoculation increased the soil-Rhizobium population and nitrogen fixation. It increased the grain yield and nodule weight by 35-43%. It also should an additve residual effect in 1995 by increasing the yield by 15%.P fertilization increased the nodule weight, grain yield, N and P uptake and nitogen nitogen content of the soil significantly. Rhizobium and phosphorus interaction was also significant for grain yield, and N and P uptake only in 1995, whereas nodule weight increased significantly during both the years. Phophorus-use efficiency was maximum with 26 kg P/ha level along with inoculation.